THE EFFECT OF HYDROTHERMAL TEMPERATURE AND UREA DOPING TIME ON THE OPTICAL PROPERTIES OF LEMONGRASS-BASED CARBON NANOPARTICLES (CNPs) - Rahmaniah Nalwi; Akhiruddin Maddu; Mersi Kurniati; Jumardin Jumardin (Jambura Physics Journal, 2023)
Carbon Nano Particles (CNPs) sourced from spiced lemongrass have been produced by the hydrothermal method at hydrothermal temperatures of 120, 140, 160 and 180 0C. The Stokes energy shift occurs due to this absorption transition and the spectrum width is determined by the electronic transition from one energy state to another. This event occurs due to the difference in energy between the two adjacent states due to the smaller vibrational state when compared to the electronic state of the CNPs.  The carbon nanoparticles (CNPs) size measurement results showed a peak value of 38.63 nm.  Functional group analysis by FTIR spectroscopy showed that the CNP consists of C=C, C-O, OH and C-N-C bonds. The Urbach energy (Eu) increased with increasing hydrothermal synthesis temperature at two hours (0.13, 0.16, 0.19 and 0.29) eV and three hours (0.12, 0.17, 0.19 and 0.28) eV. The bandgap energy (Eg) decreased with increasing hydrothermal synthesis temperature to two hours (2.30, 2.24, 2.00 and 1.92) eV and three hours (2.22, 2.20, 2.17 and 1.75) eV. The expansion of urea as a nitrogen source was carried out at a aqueous temperature of 180 0C for 2 hours and 3 hours within the blend of CNPs. The addition of urea gave a different effect on the bandgap energy (Eg) and Urbach energy (Eu) on the two CNPs. The bandgap energy (Eg) both increased from two hours (1.92 eV) to three hours (2 .22 eV), while urbach energy (Eu) decreased for a duration of two hours (3.336 eV) to three hours (3.330 eV) after adding urea. hydrothermal temperature due to synthesis time so that the structure of the CNPs becomes more stable and homogeneous